Optimasi Parameter Springback Material ST37 Pada Mesin CNC Bending TRUMPF TrumaBend V85S Menggunakan Response Surface Method - Kinari Lalitya; Pranowo Sidi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
TRUMPF TrumaBend V85S CNC Bending Machine can be used to get good bending results. But in every bending process there are several problems encountered, one of which is springback. Springback can be influenced by several parameters such as material thickness, compressive force, and bending angle, and the radius. Springback can be avoided by examining which parameters have the greatest influence. One way to improve the quality of bending products from springback is by parameter optimization. Parameter optimization is a technique used in the manufacturing process to produce the best products. Optimization of compressive force, angle, and radius parameters is done to optimize the value that can have a major effect on springback and which parameters are most influential. Design experiments using Box-Behnken with ANOVA to analyze data and performed using the Response Surface method. The results showed that the radius parameter was the only one that affected the ST37 material springback. While the optimum parameter obtained a compressive force of 500 KN, an angle of 120°, and a radius of 3 mm with a springback result of 130,28°.